PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PEKERJAAN DASAR TEKNIK OTOMOTIF PADA KELAS X TSM SMK KRISTEN KAWANGKOAN - christian binilang; Hendro Sumual; Herdy Liow (Pendidikan Teknik Mesin, 2022)
The purpose of this examination is to see the influence of learning motivation on PDTO learning outcomes in class X TSM Christian SMK Kawangkoan. The method used is quantitative research. The population is class X TSM Christian SMK Kawangkoan, totaling 28 students. The number of samples in this study were 28 students. The data in this study were collected by means of observation and questionnaires (questionnaire). After the data is collected, it is continued with simple linear regression analysis using SPSS 22. The high learning motivation that affects the learning outcomes of students in class X TSM Christian SMK Kawangkoan is 45.1% (13 students) while 54.9% is affected by other factors that are not taken researcher. The results of the analysis using the t-test or statistics with the degree of certainty (dk) = 0.05, the value of tcount = 4.618 and ttable = 2.056 so tcount> ttable. This means that H_1 is accepted and Ho is rejected. That way the results of the regression direction coefficient are real, seen from this side, the regression obtained by the researcher is significant.